Dental Restrictions to Clinical Practice during the COVID-19 Pandemic: An Australian Perspective. (July 2021) - Nguyen, T.M.; Tonmukayakul, U.; Calache, H.
The coronavirus disease 2019 (COVID-19) has disrupted essential oral healthcare in Australia. Sources for COVID-19 transmission via dental settings is considered to have high potential due to the production of aerosols and because transmission can occur through the airborne route. However, COVID-19 cases in dentistry is reportedly low. Delayed timely dental care, where severe oral diseases remain undetected, untreated, or asymptomatic such as advanced dental caries, periodontitis, and head and neck cancer, can have detrimental consequences for individuals at increased risk for oral diseases. The dental profession should remain vigilant and advocate for the continuation of essential oral healthcare even in times of uncertainty. Knowledge Transfer Statement: The reportedly low COVID-19 transmission occurring in dental settings highlight achievements made by the dental profession. There are valid reasons to reconsider risk-based essential oral healthcare during the COVID-19 pandemic.